The potential crosstalk between the brain and adipose tissue in obesity - Al-Mazeedi, Sarah; Zakareia, Faten (European Medical, Health and Pharmaceutical Journal, 2016)
Obesity is a major health problem that is increasing in an alarming rate and is associated with an increased prevalence of cardiovascular morbidity and mortality. New strategies to combat obesity epidemic are urgently needed, but gaps in understanding of obesity pathogenesis continue to limit progress in this goal. This review aims at discussing the neural aspects of obesity and the brain potential role in energy balance, also to contribute in the complex solution of obesity puzzle on neurological basis. The hypothalamic region of the brain is the center that plays an important role in the control of feeding and its related behaviors. A better understanding of its role and how it is affected by neuroendocrine and adipokines signaling might be helpful in developing new pharmacological therapy for obesity. Also, this article highlights different mechanisms by which altered brain signaling and hypothalamic inflammation predispose to diet–induced obesity.
Keywords: protein SOCS3; chuť k jídlu; zánět; ghrelin; Suppressor of Cytokine Signaling 3 Protein; adiponektin; Obesity; Leptin; energetický metabolismus; Adiponectin; lidé; Endoplasmic Reticulum; renin-angiotensin systém; Renin-Angiotensin System; Energy Metabolism; signální transdukce; Signal Transduction; Inflammation; leptin; Hypothalamus; obezita; Appetite; hypothalamus; Neuropeptides; systém hypofýza - nadledviny; Ghrelin; neuropeptidy; Pituitary-Adrenal System; NF-kappa B; endoplazmatické retikulum; Humans